Responsible innovation goes south: critique, othering, and a commitment to care - Poonam Pandey (Journal of Responsible Innovation)
This paper employs critique as othering to engage with mainstream renderings of Responsible Innovation (R(R)I) in a non-western setting. To re-image science-society relationships, initial framings of R(R)I argued for distancing from corrosive critiques of S&T and embracing democratic engagement. However, RIs fixation on Europe as its ‘Centre' led to ‘othering' and dis-engagement in the Indian context. Consequently, the critique of R(R)I by Indian actors resulted in re-framing it as ‘business-as-usual.’ I argue that rather than distancing from critique of S&T, R(R)I must revisit and deepen its commitments to care. A care-based approach demands that we continuously pay attention to the absent, neglected, and marginalized concerns without being over-invested in origins, naming, and institutionalization. The auto-ethnographical account demonstrates that embodying a critical edge (due to specific locations, entanglements, and attachments of the researcher) could generate interest, relationality, and care for neglected concerns rather than creating distance and othering.